Biallelic in-frame deletion in TRAPPC4 in a family with developmental delay and cerebellar atrophy. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Jolly, Angad; Du, Haowei; Elbendary, Hasnaa M; Jhangiani, Shalini N; Akdemir, Zeynep C; Gibbs, Richard A; Hunter, Jill V; Carvalho, Claudia M B C; Pehlivan, Davut; et al. (Brain, 2020)
Keywords: Atrophy; Cerebellar Diseases; Humans; Intellectual Disability; Sequence Deletion

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Further delineation of the clinical spectrum of KAT6B disorders and allelic series of pathogenic variants. - Zhang, Li Xin; Lemire, Gabrielle; Gonzaga-Jauregui, Claudia; Molidperee, Sirinart; Galaz-Montoya, Carolina; Liu, David S; Verloes, Alain; Shillington, Amelle G; Izumi, Kosuke; Ritter, Alyssa L; Keena, Beth; Zackai, Elaine; et al. (Genet Med, 2020)
PURPOSE: Genitopatellar syndrome and Say-Barber-Biesecker-Young-Simpson syndrome are caused by variants in the KAT6B gene and are part of a broad clinical spectrum called KAT6B disorders, whose variable expressivity is increasingly being recognized. METHODS: We herein present the phenotypes of 32 previously unreported individuals with a molecularly confirmed diagnosis of a KAT6B disorder, report 24 new pathogenic KAT6B variants, and review phenotypic information available on all published individuals with this condition. We also suggest a classification of clinical subtypes within the KAT6B disorder spectrum. RESULTS: We demonstrate that cerebral anomalies, optic nerve hypoplasia, neurobehavioral difficulties, and distal limb anomalies other than long thumbs and great toes, such as polydactyly, are more frequently observed than initially reported. Intestinal malrotation and its serious consequences can be present in affected individuals. Additionally, we identified four children with Pierre Robin sequence, four individuals who had increased nuchal translucency/cystic hygroma prenatally, and two fetuses with severe renal anomalies leading to renal failure. We also report an individual in which a pathogenic variant was inherited from a mildly affected parent. CONCLUSION: Our work provides a comprehensive review and expansion of the genotypic and phenotypic spectrum of KAT6B disorders that will assist clinicians in the assessment, counseling, and management of affected individuals.
Keywords: Blepharophimosis; Exons; Histone Acetyltransferases; Humans; Intellectual Disability; Mutation

Phenotypic expansion of POGZ-related intellectual disability syndrome (White-Sutton syndrome). - Assia Batzir, Nurit; Posey, Jennifer E; Song, Xiaofei; Akdemir, Zeynep Coban; Rosenfeld, Jill A; Brown, Chester W; Chen, Emily; Holtrop, Shannon G; Mizerik, Elizabeth; Nieto Moreno, Margarita; Payne, Katelyn; Raas-Rothschild, Annick; et al. (Am J Med Genet A, 2020)
White-Sutton syndrome (WHSUS) is a recently-identified genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ. Thus far, over 50 individuals have been reported worldwide, however phenotypic characterization and data regarding the natural history are still incomplete. Here we report the clinical features of 22 individuals with 21 unique loss of function POGZ variants. We observed a broad spectrum of intellectual disability and/or developmental delay with or without autism, and speech delay in all individuals. Other common problems included ocular abnormalities, hearing loss and gait abnormalities. A validated sleep disordered breathing questionnaire identified symptoms of obstructive sleep apnea in 4/12 (33%) individuals. A higher-than-expected proportion of cases also had gastrointestinal phenotypes, both functional and anatomical, as well as genitourinary anomalies. In line with previous publications, we observed an increased body mass index (BMI) z-score compared to the general population (mean 0.59, median 0.9; p 0.0253). Common facial features included microcephaly, broad forehead, midface hypoplasia, triangular mouth, broad nasal root and flat nasal bridge. Analysis of the Baylor Genetics clinical laboratory database revealed that POGZ variants were implicated in approximately 0.14% of cases who underwent clinical exome sequencing for neurological indications with or without involvement of other body systems. This study describes a greater allelic series and expands the phenotypic spectrum of this new syndromic form of intellectual disability and autism.
Keywords: Adolescent; Adult; Autistic Disorder; Child; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Microcephaly; Middle Aged; Mutation; Phenotype; Transposases; Whole Exome Sequencing; Young Adult

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

Biallelic Mutations in UNC80 Cause Persistent Hypotonia, Encephalopathy, Growth Retardation, and Severe Intellectual Disability. - Stray-Pedersen, Asbjørg; Cobben, Jan-Maarten; Prescott, Trine E; Lee, Sora; Cang, Chunlei; Aranda, Kimberly; Ahmed, Sohnee; Alders, Marielle; Gerstner, Thorsten; Aslaksen, Kathinka; Tétreault, Martine; Qin, Wen; et al. (Am J Hum Genet, 2016)
Ion channel proteins are required for both the establishment of resting membrane potentials and the generation of action potentials. Hundreds of mutations in genes encoding voltage-gated ion channels responsible for action potential generation have been found to cause severe neurological diseases. In contrast, the roles of voltage-independent "leak" channels, important for the establishment and maintenance of resting membrane potentials upon which action potentials are generated, are not well established in human disease. UNC80 is a large component of the NALCN sodium-leak channel complex that regulates the basal excitability of the nervous system. Loss-of-function mutations of NALCN cause infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF). We report four individuals from three unrelated families who have homozygous missense or compound heterozygous truncating mutations in UNC80 and persistent hypotonia, encephalopathy, growth failure, and severe intellectual disability. Compared to control cells, HEK293T cells transfected with an expression plasmid containing the c.5098C>T (p.Pro1700Ser) UNC80 mutation found in one individual showed markedly decreased NALCN channel currents. Our findings demonstrate the fundamental significance of UNC80 and basal ionic conductance to human health.
Keywords: Adolescent; Alleles; Brain Diseases; Carrier Proteins; Child; Child, Preschool; Female; Growth Disorders; Humans; Intellectual Disability; Membrane Proteins; Muscle Hypotonia; Mutation; Severity of Illness Index

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Yuan, Bo; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Elsea, Sarah H; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Cognitive phenotypes and genomic copy number variations. - Lupski, James R (JAMA, 2015)
Keywords: DNA Copy Number Variations; Female; Heterozygote; Humans; Intellectual Disability; Male; Mental Disorders

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Dosage changes of a segment at 17p13.1 lead to intellectual disability and microcephaly as a result of complex genetic interaction of multiple genes. - Carvalho, Claudia M B; Vasanth, Shivakumar; Shinawi, Marwan; Russell, Chad; Ramocki, Melissa B; Brown, Chester W; Graakjaer, Jesper; Skytte, Anne-Bine; Vianna-Morgante, Angela M; Krepischi, Ana C V; Patel, Gayle S; Immken, LaDonna; et al. (Am J Hum Genet, 2014)
The 17p13.1 microdeletion syndrome is a recently described genomic disorder with a core clinical phenotype of intellectual disability, poor to absent speech, dysmorphic features, and a constellation of more variable clinical features, most prominently microcephaly. We identified five subjects with copy-number variants (CNVs) on 17p13.1 for whom we performed detailed clinical and molecular studies. Breakpoint mapping and retrospective analysis of published cases refined the smallest region of overlap (SRO) for microcephaly to a genomic interval containing nine genes. Dissection of this phenotype in zebrafish embryos revealed a complex genetic architecture: dosage perturbation of four genes (ASGR1, ACADVL, DVL2, and GABARAP) impeded neurodevelopment and decreased dosage of the same loci caused a reduced mitotic index in vitro. Moreover, epistatic analyses in vivo showed that dosage perturbations of discrete gene pairings induce microcephaly. Taken together, these studies support a model in which concomitant dosage perturbation of multiple genes within the CNV drive the microcephaly and possibly other neurodevelopmental phenotypes associated with rearrangements in the 17p13.1 SRO.
Keywords: Abnormalities, Multiple; Acyl-CoA Dehydrogenase, Long-Chain; Adaptor Proteins, Signal Transducing; Animals; Asialoglycoprotein Receptor; Base Sequence; Cell Line; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human, Pair 17; Dishevelled Proteins; Flow Cytometry; Gene Dosage; Humans; Immunohistochemistry; Intellectual Disability; Microcephaly; Microtubule-Associated Proteins; Molecular Sequence Data; Phosphoproteins; Retrospective Studies; Sequence Analysis, DNA; Smith-Magenis Syndrome; Syndrome; Zebrafish

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms